Identification of Possible Causative Agents in a Polymedicated Patient Presenting With Toxic Epidermal Necrolysis. (December 2021) - Khazaka, Michael; Laverdière, Jeanne; Bouchard, Audrey; Ferreira, Victor; Mathieu, Alexandre
Purpose: To present the pharmacological evaluation process in a case of a polymedicated patient presenting with toxic epidermal necrolysis (TEN). Summary: A 75-year-old Caucasian polymedicated woman had been treated for hip pain with nonsteroidal anti-inflammatory drugs and pregabalin in the months preceding the apparition of an expanding papulo-erythematous rash. She had also started using new medicated eye drops for glaucoma. She presented to the emergency department of a regional hospital where all of her medications were stopped. The patient was transferred and admitted to a tertiary-care teaching hospital's specialized burn unit for significant cutaneous detachment. It was estimated that 70% to 80% of the body surface area was affected. Skin biopsy showed keratinocyte necrosis with a partial detachment of the epidermis leading to a diagnosis of TEN. The reaction ceased to progress 2 days after the discontinuation of her medications. A complete reepithelialization was objectified after 10 days. A series of steps were followed by the hospital pharmacist to determine which drugs were the most probable culprits. A complete pharmacological history was obtained and a timeline for medication use in the 3 months preceding rash apparition was established. A review of the literature was done to determine the drugs' relationships to Steven-Johnson syndrome or TEN. Using the algorithm of drug causality for epidermal necrolysis (ALDEN) score, it was determined that naproxen, pregabalin, and brinzolamide–timolol drops were all possible culprits. Conclusion: A systematic method for pharmacological evaluation of a polymedicated patient with TEN is presented. Naproxen, pregabalin, and brinzolamide–timolol drops were all retained as possible culprits.